Tourism Based on the Model of Strategic Place Triangle (A Case Study in Wisata Bahari Lamongan) - Wijayanto, Ismuhadi Heru; Soeaidy, M. Saleh; Rochmah, Siti (Graduate School, Universitas Brawijaya, 2014)
Tourism is a very promising prospects to support the economic development of a region. We assess Wisata Bahari Lamongan (WBL) as a tourism object. WBL was having significant decreased visitors in the last six years, thus a strategic plan is need to re-increase the number of visitors. This study used Strategic Triangle Place (SPT) model as an analysis tool to assess the strategic planning in WBL. SPT is an approach that includes three key components, namely: Positioning, Differentiation and Brand (PDB). This research used Soft System Methodology (SSM) which relevant to analyzethe strategic plan model which is expected to be recommendations from tourists on problems in WBL. The result of this showed that the strategic planning of WBL did not completely accordance with the SPT model. Positioning and differentiation elements were still weak, and the brand was not well developed. Therefore, we recommend WBL to set targeted segmentation of all social backgrounds and ages, especially children. WBL should made the sea as main differentiated factor, thus it has marine tourism potential. WBL should build an image by providing best service quality, security, comfortness, cleanliness, and best quality rides. Keywords: Strategic Planning, Strategic Place Triangle, Positioning, Differentiation, Brand